Keunggulan Kompetitif melalui Kompetensi Digital, Inovasi Financial Technologi, dan Penguatan Brand - Metris, Diksi; Lidya Pradipta Rahayu, Asmi; Muadz, Muadz; Arie Rosandy, Doni (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
In the era of digital transformation, companies are required to optimize employees' digital competencies, innovate in Financial Technology (FinTech), and strengthen their brand to achieve sustainable competitive advantage. However, there are still challenges in effectively integrating these three aspects. This research aims to analyze how employees' digital competencies contribute to competitive advantage, how FinTech innovations affect business strategies and operational efficiency, and how branding strategies can enhance customer loyalty. In addition, this research also explores the synergy between these three elements in shaping competitive advantage and identifying the main obstacles in the implementation of digitalization. This research uses qualitative methods with a literature study and document analysis approach. Data were collected from various academic journals, industry reports, and theoretical studies related to digitalization, FinTech, and brand strategies in business. The analysis was conducted using a thematic approach to identify patterns and relationships between the research variables. The research results show that employees' digital competencies enhance operational efficiency and product innovation, while the adoption of FinTech accelerates transactions, increases transparency, and supports data-driven business decisions. Additionally, a strong branding strategy contributes to increased customer loyalty through a more personalized digital experience. The synergy between these three aspects has proven to create a more solid competitive advantage, but its implementation still faces challenges such as a shortage of skilled human resources and resistance to change. Therefore, companies need to adopt a holistic digitalization strategy, develop digital competency training, and enhance technology security to ensure the sustainability of competitive advantage.